ANALYSIS OF THE NEED FOR LABOR MIGRATION POLICY IN SINGAPORE - Aruyan Suharsih Kurniasih; Muhammad Zid; Oot Hotimah (DIA: Jurnal Administrasi Publik, 2022)
Singapore is categorized as a Developed Country because of its developed trading industry among Southeast Asian countries. The existence of Singapore is inseparable from the presence of residents. As is known, most residents of Singapore are the result of migration policies due to the lack of population. Singapura recorded a record decline in people over the past year. The government's annual brief report revealed that the restrictions and conditions of the Covid-19 pandemic were one of the leading causes. Singaporean population also fell 0.7% to 3.5 million, while permanent residents (PR) fell 6.2% to 0.49 million. This is the first drop from YoY, both in population and population since data was collected in 1970. Migration is the movement of people from one area to another aimed at living sedentary, which goes beyond the administrative/political boundaries. The move made by a resident is usually immigrant because he has the desire to live a sedentary life for a long time. This research uses a qualitative descriptive method with literature review research. The results showed that one of the factors driving migration from Indonesia to Singapore was the lack of labor in Singapore. The process of self-formation into a Singaporean identity through migration, adaptation, and integration stages. Singapore has a policy toward migrant workers. The policy is specifically related to skills and age. If workers’ skills do not meet the criteria, the Government applies a policy to upgrade skills by conducting certified training. The Basic Skill Certificate (BSC) and Skill Evaluation Certificate (SEC) have been implemented since 1998.